The Correspondence of Erasmus : Letters 2940 to 3141, Volume 21. - Erasmus, Desiderius, -1536 (Book collections on Project MUSE., 1974)
The aim of the Collected Works of Erasmus is to make available an accurate, readable English text of Erasmus' correspondence and his other principal writings in an edition of 89 volumes. Erasmus was one of the architects of modern thought and his works reflect a vast range of interests including history, theology, the classics, social theory, education, political theory, literature, and the history of ideas. His letters remain the single most important source for the intellectual history of the Renaissance and Reformation. -- Publisher.